Influence of tetracycline on the microbial community composition and activity of nitrifying biofilms - Matos, M. I. (2014)
The present work aims to evaluate the bacterial composition and activity (carbon and nitrogen removal) of nitrifying biofilms exposed to 50 μg L−1 of tetracycline. The tetracycline removal efficiency and the occurrence of tetracycline resistance (tet) genes were also studied. Two sequencing batch biofilm reactors (SBBRs) fed with synthetic wastewater were operated without (SBBR1) and with (SBBR2) the antibiotic. Both SBBRs showed similar organic matter biodegradation and nitrification activity. Tetracycline removal was about 28% and biodegradation was probably the principal removal mechanism of the antibiotic. Polymerase chain reaction-denaturing gradient gel electrophoresis analysis of the bacterial community showed shifts leading to not only the fading of some ribotypes, but also the emergence of new ones in the biofilm with tetracycline. The study of the tet genes showed that tet(S) was only detected in the biofilm with tetracycline, suggesting a relationship between its occurrence and the presence of the antibiotic.